Implementation Of Final Sanctions On Murabahah Akad At Mandiri Sharia Bank - Khoirul Ichfan; Junaidi Junaidi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam syarifuddin Lumajang, 2022)
The development of Islamic banks in Indonesia is quite significant, this is indicated by the increasing number of Islamic banking institutions that have been established. From a number of Islamic bank products, the most widely used is murabahah financing products. To avoid losses suffered by Islamic banking due to delays in customer payments for their maturing obligations, especially in murabahah contracts, a provision is made regarding the application of sanctions by taking a number of assets as a fine for delays made by customers, with the aim of providing a deterrent effect to people who are able but delaying payments. This paper uses a descriptive method of application from secondary data sources in the form of books, articles and documents from the internet either from websites or other valid sources.